Can a Quantum Electron Microscope Achieve Low - Damage (Biological) Imaging? - Thomas, Sebastian; Hammer, Jakob; Weber, Philipp; Hommelhoff, Peter (Microscopy and Microanalysis, 2015)

Designs for a quantum electron microscope - Kruit, Pieter; Hobbs, Richard G.; Kim, Chung-Soo; Yang, Yujia; Manfrinato, Vitor R.; Hammer, Jakob; Thomas, Sebastian; Weber, Philipp; Klopfer, Brannon; Kohstall, Christoph; Juffmann, Thomas; Kasevich, Mark A.; et al. (Ultramicroscopy, 2016)
One of the astounding consequences of quantum mechanics is that it allows the detection of a target using an incident probe, with only a low probability of interaction of the probe and the target. This 'quantum weirdness' could be applied in the field of electron microscopy to generate images of beam-sensitive specimens with substantially reduced damage to the specimen. A reduction of beam-induced damage to specimens is especially of great importance if it can enable imaging of biological specimens with atomic resolution. Following a recent suggestion that interaction-free measurements are possible with electrons, we now analyze the difficulties of actually building an atomic resolution interaction-free electron microscope, or "quantum electron microscope". A quantum electron microscope would require a number of unique components not found in conventional transmission electron microscopes. These components include a coherent electron beam-splitter or two-state-coupler, and a resonator structure to allow each electron to interrogate the specimen multiple times, thus supporting high success probabilities for interaction-free detection of the specimen. Different system designs are presented here, which are based on four different choices of two-state-couplers: a thin crystal, a grating mirror, a standing light wave and an electro-dynamical pseudopotential. Challenges for the detailed electron optical design are identified as future directions for development. While it is concluded that it should be possible to build an atomic resolution quantum electron microscope, we have also identified a number of hurdles to the development of such a microscope and further theoretical investigations that will be required to enable a complete interpretation of the images produced by such a microscope.
Keywords: Interaction free measurement; Quantum electron microscope; Quantum interrogation; Radiation damage; Transmission electron microscope

Fibre-based pressure-controlled sources for quantum optics - Joly, Nicolas; Hammer, Jakob; Chekhova, Maria (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We present progress towards the generation of photon triplet states and realisation of a tunable source of entangled photons. In both cases, control of the phase-matching is achieved through gas-pressure tuning.
CRIS-Team Scopus Importer:2021-12-24

Highly Coherent Electron Beam from a Laser-Triggered Tungsten Needle Tip. - Ehberger, Dominik; Hammer, Jakob; Eisele, Max; Krüger, Michael; Noe, Jonathan; Högele, Alexander; Hommelhoff, Peter (Physical Review Letters, 2015)
We report on a quantitative measurement of the spatial coherence of electrons emitted from a sharp metal needle tip. We investigate the coherence in photoemission triggered by a near-ultraviolet laser with a photon energy of 3.1 eV and compare it to dc-field emission. A carbon nanotube is brought into close proximity to the emitter tip to act as an electrostatic biprism. From the resulting electron matter wave interference fringes, we deduce an upper limit of the effective source radius both in laser-triggered and dc-field emission mode, which quantifies the spatial coherence of the emitted electron beam. We obtain (0.80±0.05) nm in laser-triggered and (0.55±0.02) nm in dc-field emission mode, revealing that the outstanding coherence properties of electron beams from needle tip field emitters are largely maintained in laser-induced emission. In addition, the relative coherence width of 0.36 of the photoemitted electron beam is the largest observed so far. The preservation of electronic coherence during emission as well as ramifications for time-resolved electron imaging techniques are discusse

Microwave chip-based beam splitter for low-energy guided electrons - Hammer, Jakob; Thomas, Sebastian; Weber, Philipp; Hommelhoff, Peter (Physical Review Letters, 2015)
We present a novel beam splitter for low-energy electrons using a micro-structured guiding potential created above the surface of a planar microwave chip. Beam splitting arises from smoothly transforming the transverse guiding potential for an electron beam from a single-well harmonic confinement into a double well, thereby generating two separated output beams with 5 mm lateral spacing. Efficient beam splitting is observed for electron kinetic energies up to 3 eV, in excellent agreement with particle tracking simulations. We discuss prospects of this novel beam splitter approach for electron-based quantum matter-wave optics experiments.

Phase-Resolved Electron Guiding in Optimized Chip-Based Microwave Potentials - Hammer, Jakob; Hoffrogge, Johannes; Heinrich, Stephan; Hommelhoff, Peter (Physical Review Applied, 2014)
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.exphys.phaser

Recent experimental results and future directions of the DLA single grating project - McNeur, Joshua; Hammer, Jonas; Li, Ang; Tafel, Alexander; Hommelhoff, Peter; Tafel, Alexander; Hammer, Jakob (16th Advanced Accelerator Concepts Workshop, AAC 2014, 2016)
The recent demonstration of Dielectric Laser Acceleration of subrelativistic electrons is reviewed. In this experiment, a Ti:Sapphire laser is incident upon a fused silica grating, exciting fields that accelerated 28 keV electrons with a 25 MeV/m acceleration gradient. Upgrades and future directions of this DLA project are discussed.

Tip-based source of femtosecond electron pulses at 30 keV - Hoffrogge, Johannes; Stein, Jan Paul; Krüger, Michael; Förster, Michael; Hammer, Jakob; Ehberger, Dominik; Baum, Peter; Hommelhoff, Peter (Journal of Applied Physics, 2014)
We present a nano-scale photoelectron source, optimized for ultrashort pulse durations and well-suited for time-resolved diffraction and advanced laser acceleration experiments. A tungsten tip of several-ten-nanometers diameter mounted in a suppressor-extractor electrode configuration allows the generation of 30 keV electron pulses with an estimated pulse duration of 9 fs (standard deviation; 21 fs full width at half maximum) at the gun exit. We infer the pulse duration from particle tracking simulations, which are in excellent agreement with experimental measurements of the electron-optical properties of the source in the spatial domain. We also demonstrate femtosecond-laser triggered operation of the apparatus. The temporal broadening of the pulse upon propagation to a diffraction sample can be greatly reduced by collimating the beam. Besides the short electron pulse duration, a tip-based source is expected to feature a large transverse coherence and a nanometric emittance. © 2014 AIP Publishing LLC.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.exphys.tipbas